(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The article examines the socio-economic significance of educational services in the development of Uzbekistan’s economy. Special attention is paid to the role of education in the formation of human capital, the training of a qualified workforce, the improvement of national competitiveness and the enhancement of living standards. The paper also considers strategic initiatives of the Republic of Uzbekistan aimed at reforming the education system, developing the private sector of educational services and introducing information and communication technologies into the educational process.